A high-nuclearity complex containing a decanuclear iron(iii)/oxo cage in a football-like structure and rare (R-/S)-hemiacetalate ligands in a butterfly-like format. Issue 68 (4th December 2019) - Zheng, Chunying; Liang, Mingyue; Sun, Haofen; Ma, Jiping; Bi, Xuejun; Zhao, Yang; Tan, Weiqiang; Li, Hui
Abstract : The employment of pyridine-2-carboxaldehyde in high-nuclearity cluster chemistry has provided access to a decanuclear iron(iii )/oxo cage in football-like structure and unusual ( R -/ S )-hemiacetalate ligands in butterfly-like format. Abstract : A challenge in the field of high nuclearity Fe(iii )/oxo cluster chemistry remains the development of new synthetic methods to such molecules. In this work, the employment of pyridine-2-carboxaldehyde (py-2-al) in high-nuclearity transition-metal cluster chemistry has provided access to an unprecedented decanuclear iron(iii ) complex, [Fe10 (NO3 )7 (O)6 (OH0.5 )2 (( S )-py-hemi)4 (( R )-py-hemi)4 ]·4H2 O (1 ) (( R -/ S )-py-hemi = ( R -/ S )-pyridine-2-carboxaldehyde hemiacetalate). The synthesis, beautiful structure and the physical characterization (thermal gravimetric analysis, X-ray powder diffraction, proton nuclear magnetic resonance, magnetic susceptibility) of complex 1 are described in this contribution. Complex 1 provides a new route to obtain high nuclearity magnetic clusters with beautiful structures.